Legal perspective on the risk of copyright infringement by AI-generated contents in China - Tong, Zhou; Mohamad Rizal Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2024)
The swift progress of Artificial Intelligence (AI) technology is driving advancements in the internet and cultural sectors, but it also poses challenges to traditional laws, especially copyright law. This article examines the legal complexities associated with AI-generated products and copyright infringement risks in the Chinese internet context. By combining the Copyright Law of the People's Republic of China and analyzing relevant judicial dispute cases in China, this study explores generative artificial intelligence models for generating creative content such as text, images, and music, and introduces their basic technical mechanisms. Focusing on how AI uses existing copyrighted material to generate new works, discuss the issue of attribution of authorship of AI-generated works and its impact on traditional copyright principles. Generative AI is at risk of copyright infringement through the use of machine learning and deep learning technologies to capture data on the Internet for a wide range of creative training. Although China does not have clear legal provisions on copyright ownership and authorship of generative AI, the legal definition of ‘work’ adds a new protective interpretation of generative AI. The study suggests that the loopholes in copyright infringement risks can be closed by improving and reforming China's copyright law, or judicial interpretation of AI, to promote the development of AI technology and keep the law up to date. The comprehensive legal framework not only protects the rights of copyright owners and encourages technological innovation, but also improves China's competitiveness in the global digital economy.